Modified moving-average crossover trading strategy: evidence in Malaysia equity market - Soh, Chuen Yean (2016)
This study examine the profitability of technical analysis using the most renowned trendfollowing tool, the original moving-average (MA) crossover strategy, to compare with the conventional simple buy-and-hold strategy, using the evidence from Malaysia equity market the FBMKLCI Index from 2000 to 2014. Specifically, this study investigates the performance of the original moving-average strategy and a modified moving-average crossover strategy with additional trading rules such as entry rule, exit rule, holding rule, and stop-loss rule. The results in this study are consistent to past studies that stronglysupport moving-average crossover trading strategies. The result here suggests that all combinations of short-MA and long-MA periods of the original MA crossover strategy and majority combinations of short-MA and long-MA of the modified MA crossover strategy outperform market benchmark with higher risk-adjusted return. In addition, the 1-period short-MA demonstrates the best return in both original and modified moving-average crossover strategy; better still the modified strategy outperforms the original strategy with lower frequency of trades which could largely reduce transaction costs and with lower return distribution variability.